2020
DOI: 10.3389/fneur.2020.591526
|View full text |Cite
|
Sign up to set email alerts
|

Higher Prevalence and Age Susceptibility of Intracranial Aneurysm in Patients With Acoustic Neuroma

Abstract: Introduction: The purpose of this study was to verify whether the prevalence of intracranial aneurysm (IA) in patients with acoustic neuroma is greater than that in age-and sex-matched controls and to evaluate the independent risk factors related to the occurrence of IA. Methods: We retrospectively analyzed 231 patients diagnosed with acoustic neuroma at our institute between 2015 and 2019 and 489 controls from the medical examination center. Cerebrovascular angiography was acquired from all subjects to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Age is one of the most essential risk factors in cerebrovascular diseases [15][16] , such as cerebral infarction 17 , transient ischemic attack (TIA) 18 , Intracerebral hemorrhage (ICH) 19 , and intracranial aneurysm 20 . Our study also found age was an independent predict factors for the prognosis of cerebral infarction patients in intensive care units.…”
Section: Discussionmentioning
confidence: 99%
“…Age is one of the most essential risk factors in cerebrovascular diseases [15][16] , such as cerebral infarction 17 , transient ischemic attack (TIA) 18 , Intracerebral hemorrhage (ICH) 19 , and intracranial aneurysm 20 . Our study also found age was an independent predict factors for the prognosis of cerebral infarction patients in intensive care units.…”
Section: Discussionmentioning
confidence: 99%